Mathematics Teachers’ Levels of ICT Expertise and Use and Their Beliefs about ICT Integration and Students’ Problem-Solving Skills - Mark Joseph Deblois Pastor; Lily Ann Cabanilla Pedro (Southeast Asian Mathematics Education Journal, 2023)
This study aimed to determine the relationship between the secondary Mathematics teachers’ level of ICT expertise, level of ICT use and students’ problem-solving skills. It employed two data collection tools: the Mathematics Teachers' Survey Questionnaire (MTSQ) and the Mathematics Assessment on Problem Solving (MAPS). The samples encompassed 40 Grade 7 Mathematics teachers and 2,439 Grade 7 students from three school divisions in Ilocos Norte, Philippines. The results demonstrated that teachers are highly competent in basic ICT skills and applications, and they have positive beliefs about the use of ICT in teaching. However, because preparing ICT-enriched instruction takes more time, they only use ICT in teaching once or twice a week on average. According to the study's findings, teachers who are younger and have attended more ICT-related training are better equipped with ICT skills, use ICT in classroom instruction more frequently, and have a better disposition towards ICT integration in teaching. The study further discovered that when teachers believe they have a high level of ICT expertise, they are more likely to use ICT in their classrooms. Similarly, when teachers are more knowledgeable about using ICT, they are more inclined to support ICT integration in the classroom. Notably, the study reveals that students' problem-solving skills are significantly related to teachers' level of expertise, level of ICT use, and their beliefs about ICT integration.